Environmental investigation of the quantitative distribution of bioaerosols in public indoor spaces – A case study in Korea - Ji-You Kwoun; Seok Won Kang; Yanjun Wang; Tae Jung Lee; Young Min Jo (Indoor Environments, 2025)
Bioaerosols, including airborne bacteria and fungi, are widely distributed in the indoor environments causing adverse effects on human health. Bioaerosols suspended in six types of public indoor spaces categorized by the government were investigated in 12 facilities in a large metropolitan area of Korea. A total of 245 samples provided evidence of a close dependency on indoor humidity in addition to the numbers of occupants. Childcare centers had high concentrations of bioaerosols (26 CFU/m3 to 2916 CFU/m3), indicating high risk of exposure with 120.2 CFU/kg. The indoor bioaerosol level was high mostly in summer rather than winter. The results of this study provide valuable information on air quality management and microbial pollution control in urban public spaces. Implications and impacts: − Bio-contamination of public indoor spaces is being of interests particularly in metro-cities. − Field identification of bioaerosol levels will help in establishing the preventive policy. − Consistent accumulation of field data is essential for improving the indoor environment.